Association of High Blood Homocysteine and Risk of Increased Severity of Ischemic Stroke Events - Harris, Salim; Rasyid, Al; Kurniawan, Mohammad; Mesiano, Taufik; Hidayat, Rakhmad (International Journal of Angiology, 2019)
Stroke is the leading cause of death and disability in the world as well as in Indonesia. Initial stroke severity is an important factor that affects short- and long-term stroke outcomes. This cross-sectional study was conducted in Cipto Mangunkusumo Hospital from July 2017 to January 2018 to investigate the factors that affect stroke severity. A total of 77 acute ischemic stroke patients were divided into three groups, which include low blood homocysteine levels (< 9 μmol/L), moderate blood homocysteine levels (9–15 μmol/L), and high blood homocysteine levels (> 15 μmol/L). The acquired data were analyzed using Kruskal–Wallis test and a significant difference of initial National Institute of Health Stroke Scale (NIHSS) and blood homocysteine levels (H = 13.328, p = 0.001) were seen, with a mean rank of 25.86 for low blood homocysteine levels, 33.69 for moderate blood homocysteine levels, and 48.94 for high blood homocysteine levels. The patients were then divided into two groups based on the NIHSS (≤5 and > 5) to calculate the risk correlation of blood homocysteine levels and NIHSS by using regression. We found that patients with high blood homocysteine levels had 14.4 times higher risk of having NIHSS > 5 compared with those with low blood homocysteine levels (p = 0.002, 95% confidence interval [CI] [2.714–76.407]), and 3.9 times higher risk compared with those with moderate blood homocysteine levels (p = 0.011, 95% CI [1.371–11.246]). We concluded that homocysteine is a risk factor for a higher stroke severity. Future studies to evaluate the usefulness of homocysteine-lowering therapy in stroke patients are recommended.
Keywords: acute ischemic stroke; homocysteine; NIHSS; stroke severity